2013
DOI: 10.1186/1475-2875-12-266
|View full text |Cite
|
Sign up to set email alerts
|

The use of non-prescribed anti-malarial drugs for the treatment of malaria in the Bolgatanga municipality, northern Ghana

Abstract: BackgroundThe use of non-prescribed anti-malarial drugs can lead to treatment failure and development of drug-resistant parasites. This study investigated the use of non-prescribed anti-malarial drugs for the treatment of malaria in the Bolgatanga Municipality of northern Ghana.MethodsThis was a cross-sectional survey of a random sample of 392 adults and children with episodes of malaria in the last four weeks prior to the study.ResultsMajority of survey respondents 96.9% (380) knew the symptoms of malaria, 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
7
16
0
Order By: Relevance
“…Other sources of unprescribed drugs were what remained from previous illness, from friends/relatives and the shops. These findings are similar to those reported locally in Kenya (Deressa, et al 2003;Buabeng, et al 2007;Aborah, et al 2013). Sourcing medications from what remained in previous illness, friends/relatives and local shops is alarming because these sources indicate possible overdose, under dose, poor adherence to recommended prescription.…”
Section: Discussionsupporting
confidence: 81%
“…Other sources of unprescribed drugs were what remained from previous illness, from friends/relatives and the shops. These findings are similar to those reported locally in Kenya (Deressa, et al 2003;Buabeng, et al 2007;Aborah, et al 2013). Sourcing medications from what remained in previous illness, friends/relatives and local shops is alarming because these sources indicate possible overdose, under dose, poor adherence to recommended prescription.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, the study revealed that high proportion of the respondents (73%) practiced self-medication for malaria treatment. The observation is congruent with findings elsewhere [31][32][33]. This finding contrasts gravely with what obtained in a study carried out among non-medical tertiary students in Osun State, Nigeria, where only 5.7% practiced self-medication [27].…”
Section: Discussionsupporting
confidence: 80%
“…The emergence of these rare mutations in Anonkoua-kouté suggests that monitoring SP resistance during SP/IPTp implementation will be important. In line with previous work in Mali and Ghana [15,20,31] the increased number of mutant alleles at key loci of the pfdhfr and pfdhps genes in Anonkoua-kouté reflects a long history of the usage of sulpha drugs including SP consistent with the level of SP in West Africa [15,20,31]. This provides evidence for an ongoing selection of resistant parasites [32] due to the intensive use of sulpha drugs such as Trimethoprim-Sulfadoxine in the treatment of fever associated with respiratory affections in children less than 15 years or against opportunistic infections occurring in individuals infected with HIV/ AIDS [33].…”
Section: Discussionsupporting
confidence: 74%
“…Since it is recommended for the intermittent preventive treatment in pregnant women [18], SP is still accessible for acute malaria treatment especially from the informal sector [19,20].…”
Section: Discussionmentioning
confidence: 99%